Knowledge and Perception of Rabies among School Children in Rabies Endemic Areas of South Bhutan - Lungten, Lungten; Rinchen, Sangay; Tenzin, Tenzin; Phimpraphai, Waraphon; de Garine-Wichatitsky, Michel (Tropical medicine and infectious disease, 2021)
Rabies is endemic in southern Bhutan and children are the frequent victims of dog bites. We surveyed the knowledge, attitude, and practices on rabies among school children in three schools located in southern Bhutan. A total of 701 students (57.9% female, 42.1% male) with an age range of 12–21 years (mean: 15 years) participated in the survey, of which 98.2% had heard about rabies. Most of the students demonstrated a good level of knowledge (59.7%) and a favorable perception towards rabies (57.7%). Multivariable logistic analysis revealed the relation between knowledge and the awareness campaign (OR:1.5, 95% CI: 1.1–2.1). Similarly, higher grades of students (OR:1.9, 95%CI: 1.3–2.9) and employed mothers of the students (OR: 1.6, 95% CI: 1.0–2.7) were associated with more favorable perceptions. However, some knowledge gaps were identified in this study, such as students not being able to clearly mention the susceptible hosts of rabies, transmission routes, clinical signs, and prevention and control options. Therefore, regular awareness programs on rabies are necessary among school children in Bhutan.